The wages of sin - Welsh, Kaite (Pegasus Crime, 2017)
"Sarah Gilchrist fled London and a troubled past to join the University of Edinburgh's medical school in 1892, the first year it admitted women. Determined to become a doctor despite the misgivings of her family and society, Sarah quickly finds plenty of barriers at school itself; professors who refuse to teach their new pupils, male students determined to force out their female counterparts, and-- perhaps worst of all-- female peers who will do anything to avoid being associated with a fallen woman. Desperate for a proper education, Sarah turns to one of the city's ramshackle charitable hospitals for additional training. The Saint Giles Infirmary for Women ministers to the downtrodden and drunk, the thieves and whores with nowhere else to go. There, Sarah gets quite an education, but when Lucy-- a prostitute and one of Sarah's patients-- turns up in the university dissecting room as a battered corpse, Sarah finds herself drawn into a murky underworld of bribery, brothels, and body snatchers. Painfully aware of just how little separates her own life from that of her former patient's, Sarah is determined to find out what happened to Lucy and to bring those responsible for her death to justice. But as Sarah searches for answers in Edinburgh's dank alleyways, bawdy houses, and fight clubs, she comes closer and closer to uncovering one of Edinburgh's most lucrative trades-- and, in doing so, puts her own life at risk" -- Dust jacket flap